2018
DOI: 10.1111/geb.12727
|View full text |Cite
|
Sign up to set email alerts
|

Mountain roads and non‐native species modify elevational patterns of plant diversity

Abstract: Aim: We investigated patterns of species richness and community dissimilarity along elevation gradients using globally replicated, standardized surveys of vascular plants. We asked how these patterns of diversity are influenced by anthropogenic pressures (road construction and non-native species). Location: Global.Time period: 2008-2015.Major taxa studied: Vascular plants.Methods: Native and non-native vascular plant species were recorded in 943 plots along 25 elevation gradients, in nine mountain regions, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 61 publications
6
93
2
10
Order By: Relevance
“…The non‐significant pattern recorded for natives is probably due to the truncated elevation gradient of this study (c. 1,200 m), which was too short to capture the hump‐shaped elevational pattern of native plants often found in studies that included wider gradients (Marini et al, ; Guo et al, ). As expected from previous studies (Pauchard et al, ; Seipel, Alexander, Edwards, & Kueffer, ; Haider et al, ), we found a strong negative relationship between the number of exotics and elevation. This pattern may be explained by a combination of two factors: (a) higher propagule pressure in the lowlands, and (b) temperature constraints at higher elevations (Becker et al, ; Alexander et al, ;).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The non‐significant pattern recorded for natives is probably due to the truncated elevation gradient of this study (c. 1,200 m), which was too short to capture the hump‐shaped elevational pattern of native plants often found in studies that included wider gradients (Marini et al, ; Guo et al, ). As expected from previous studies (Pauchard et al, ; Seipel, Alexander, Edwards, & Kueffer, ; Haider et al, ), we found a strong negative relationship between the number of exotics and elevation. This pattern may be explained by a combination of two factors: (a) higher propagule pressure in the lowlands, and (b) temperature constraints at higher elevations (Becker et al, ; Alexander et al, ;).…”
Section: Discussionsupporting
confidence: 91%
“…First, the absence of exotic species in disturbed sites at high elevations may be due to the small scale at which the disturbance was performed (1 m 2 ). Studies encompassing a larger spatial scale have found that exotic species are frequent at high elevations also, especially when the disturbance was severe (Haider et al, ). Additionally, our study observed establishment dynamics within one year, and therefore we were not able to detect long‐term changes in the community.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations